Thermal transmission of water-based rotating nano fluid flow over an exponentially sprawling sheet with the clout of partial slip condition and variable viscosity - Azad Hussain; Ali Mujtaba; M.Y. Malik; Ali Saeed Alqahtani; Muhammad Naveel Riaz Dar (Results in Engineering)
The aim of this study is to describe the effects of a revolving Nano-liquid on an exponentially extending surface. A 3-D, steady, incompressible, rotating Nano-fluid flow over on an exponentially sprawling sheet. Two distinct kinds of tiny particles, titanium oxide and zinc oxide (ZnO andTiO2), are employed in this investigation, with water as base fluid. The analytical solution is evaluated using MATLAB's built-in solver, bvp4c.The graphs illustrate the evaluation of the velocity and temperature attributes for the rotation parameter, slip parameter, and variable viscosity for both types of nanoparticles. Data show the numerical value of various Nusselt numbers and skin friction index-related factors. For the values of slip parameter K = 0.1 heat transfer rate for ZnO Nano-fluid is 3.3% and heat transfer rate for TiO2 is 1.4%. In rotating machinery like wheels, gears, and turbines, Nano-fluids can be employed as lubrication. The load-lifting capability, abrasion, and system performance can all be improved by adding Nano-materials to the lubricant fluid. Rotating Nano-fluids can be used for hyperthermia treatment and drug delivery in the field of biomedical engineering.